Burying the Stability Pact: The Reanimation of Default Risk in the Euro Area - Christian Fahrholz; Roman Goldbach (Graduiertenkolleg 'Konstitutionelle Grundlagen globalisierter Finanzmärkte - Stabilität und Wandel', 2010)
After neutering the Stability and Growth Pact (SGP) in 2005, recent developments pinpoint that financial markets considerably discriminate between qualities of European governmental borrowers. In this article we inquire whether and to what extent political statements and decisions within the realm of the Europe an Union (EU) have deteriorated the effectiveness of the SGP from financial markets' perspective. The SGP may represent a focal point in financial market actors' calculus regarding long-term public debt formation. Accordingly, any news – such as political rhetoric in context of the SGP – affects financial market actors' evaluation concerning governmental creditworthiness. We use financial market data to measure the influence that political events exert on governmental default risks. Using daily data for the EMU memberstates from 2002 to 2005 the analysis reveals that political rhetoric has considerably undermined the efficacy of the SGP. In turn, market forces have regained some more momentum. According policy implications are outlined.
urn:nbn:de:gbv:27-20100727-141823-4
Keywords: E62; G12; G14; H30; H61; 330; Europäischer Stabilitätsmechanismus; Politik; Öffentlichkeitsarbeit; Länderrisiko; Staatsbankrott; Eurozone